Circadian Phase Assessment of Core Body Temperature Using a Wearable Temperature Sensor Under the Real World - Naoko Kubota; Kazufumi Okada; Yujiro Yamanaka (Sleep Science)
Objective To evaluate whether a patch-type wearable temperature sensor (CALERA Research) could determine the circadian phase of core body temperature (CBT) in a manner like a rectal probe.